Do Independent Commissioners, Board Size, and Audit Committees Matter for ROA? Evidence from IDX Basic & Chemical, 2019–2023 - Sutarti Sutarti; Lisa Silvia; Bambang Pamungkas (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the effects of independent commissioners, board of directors, and audit committee on financial performance, proxied by return on assets (ROA), among manufacturing firms in the basic & chemical subsector listed on the Indonesia Stock Exchange during 2019–2023. Secondary data were collected from published annual and financial reports. Using a quantitative approach, the analysis employs linear regression with classical assumption tests and t and F statistics. The results reveal that board size has a positive and significant effect on ROA, whereas the proportion of independent commissioners and the size of the audit committee show negative but insignificant effects. Jointly, the three governance mechanisms significantly influence financial performance. These findings suggest that board configuration—particularly an adequate board size—plays a more salient role in enhancing accounting performance in the chemical-based industry than the other two mechanisms. The study provides practical implications for firms and regulators to align board composition with operational complexity and contributes updated evidence from Indonesia’s basic & chemical context.   Keywords: corporate governance, independent commissioners, board of directors, audit committee, ROA, basic & chemical manufacturing.